Pyogranulomatous panniculitis in a cat associated with infection by the Mycobacterium fortuitum/peregrinum group - Youssef, Sameh (2002)
A 6-year-old, spayed female, American domestic shorthair was presented with a 10-month history of nodules on the dorsum. Diagnosis of pyogranulomatous panniculitis caused by Mycobacterium fortuitum/peregrinum group was achieved by using tissue culture, chromatography, and histopathologic examination. Pathological findings, diagnosis, and clinical management of the condition are discussed.